Recent advances in materials and applications for bioelectronic and biorobotic systems. Issue 3 (21st February 2022) - Phillips, Jacob W.; Prominski, Aleksander; Tian, Bozhi
Abstract: The ultimate goal of the advancements in bioelectronics and robotics is the creation of seamless interfaces between artificial devices and biological structures. Current efforts in this area have been focused on designing biocompatible, mechanically compliant, and minimally invasive electronic and robotic systems for a range of applications, such as motor control and sweat sensing. The purposeful design of bioelectronic and robotic systems using the principles of biomimicry enables the creation of biocompatible and life‐like machines and electronics. The success of such approaches relies on the new development and applications of soft materials, as well as methods of actuation and sensing that are inspired, either by composition, function, or properties, of the naturally occurring organisms. A combination of rigid structural components, soft actuators, and flexible sensors can enable the integration of such devices with biological organisms and eventually human users. In this review, we highlight the recent advances in biomimetic soft robotics and bioelectronics. We describe the soft robotic fabrication toolbox and modern solution in bioelectronics that, in our opinion, will enable the fusion of these fields by creating robotic bioelectronic systems. Future development in this area will require substantial integration of adaptable and responsive components at the biointerfaces. Abstract : The merging of bioelectronics and robotics may allow the creation of seamless interfaces between artificial devices and biological structures. The purposeful design of bioelectronic and robotic systems using the principles of biomimicry enables the creation of biocompatible and life‐like machines and electronics. In this review, we highlight the recent advances in biomimetic soft robotics and bioelectronics.